Efektifitas Hypnobirthing Terhadap Penurunan Nyeri Persalinan: Systematic Literatur Review - Engly Nichlas; Yustina Ananti; Tri Budy Rahayu (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: Labor pain is a subjective experience of physical sensations associated with uterine contractions, cervical dilatation and effacement, and fetal descent during labor. According to survey results, an average of 90% of mothers who give birth will experience labor pain. The World Health Organization states that about 13% of mothers do not want to feel labor pain. Hypnobirthing is an autohypnosis technique, which is an effort to instill positive intentions through suggestions into the soul or subconscious mind during pregnancy and preparation for childbirth. Hypnobirthing can create calm and relaxed conditions that support physical, muscle, emotional and mental relaxation at the time of delivery so that labor is expected to be passed well without trauma. The purpose of the study was to determine the effectiveness of hypnobirthing on reducing labor pain by means of a systematic review of the literature review. Methods: Using a systematic literature review method with a meta-synthetic approach. Data collection techniques through searches on the PubMed, ScienceDirect and Google Scholar databases, consisting of international and national journals that meet the inclusion and exclusion criteria, obtained 12 journals, published in 2012-2021. Results: The results of the journal analysis showed the effectiveness of hypnobirthing in reducing labor pain. The pain level of the intervention and control groups before being given the hypnobirthing technique on average experienced severe and moderate pain, while the level of pain in the intervention group after being given the hypnobirthing technique decreased to moderate pain and mild pain.Conclusion: hypnobirthing is effective in reducing labor pain.